Skull Modeling Effects in Conductivity Estimates Using Parametric Electrical Impedance Tomography - Fernández Corazza, Mariano (2017)
Objective: To estimate scalp, skull, compact bone, and marrow bone electrical conductivity values based on electrical impedance tomography (EIT) measurements, and to determine the influence of skull modeling details on the estimates. Methods: We collected EIT data with 62 current injection pairs and built five 6–8 million finite element (FE) head models with different grades of skull simplifications for four subjects, including three whose head models serve as Atlases in the scientific literature and in commercial equipment (Colin27 and EGI’s Geosource atlases). We estimated electrical conductivity of the scalp, skull, marrow bone, and compact bone tissues for each current injection pair, each model, and each subject. Results: Closure of skull holes in FE models, use of simplified four-layer boundary element method-like models, and neglecting the CSF layer produce an overestimation of the skull conductivity of 10%, 10%–20%, and 20%–30%, respectively (accumulated overestimation of 50%–70%). The average extracted conductivities are 288 ± 53 (the scalp), 4.3 ± 0.08 (the compact bone), and 5.5 ± 1.25 (the whole skull) mS/m. The marrow bone estimates showed large dispersion. Conclusion: Present EIT estimates for the skull conductivity are lower than typical literature reference values, but previous in vivo EIT results are likely overestimated due to the use of simpler models. Significance: Typical literature values of 7–10 mS/m for skull conductivity should be replaced by the present estimated values when using detailed skull head models. We also provide subject specific conductivity estimates for widely used Atlas head models.